Prevalence of epilepsy in Bangladesh: Results from a national household survey. Issue 4 (18th September 2020) - Mohammad, Quazi Deen; Saha, Narayan Chandra; Alam, Md Badrul; Hoque, Seikh Azimul; Islam, Ariful; Chowdhury, Rajib Nayan; Hussain, Mohammad Enayet; Chowdhury, Yamin Shahriar; Hossain, Sakhawat; Chowdhury, Mahmood Ahmed; Rahman, Matiur; Majumder, Bikash Kumar; et al.
Abstract: Objective: To determine the prevalence and types of epilepsy in Bangladesh. Methods: We conducted a nationwide population‐based cross‐sectional survey among Bangladeshi population of all ages, except children under one month. We surveyed 9839 participants (urban, 4918; rural, 4920) recruited at their households using multistage cluster sampling. Trained physicians with neurology background confirmed the diagnosis of suspected epilepsy cases identified by interviewer‐administered questionnaires. We reported the overall and sex, residence, and age groups‐specific prevalence of epilepsy per 1000 populations with 95% confidence interval. Results: The national prevalence of epilepsy per 1000 was 8.4 (95% CI 5.6‐11.1), urban 8.0 (4.6‐11.4), and rural 8.5 (5.60‐11.5). The prevalence in adult males and females was 9.2 (5.7‐12.6) and 7.7 (3.6‐11.7), respectively. The prevalence in children aged <18 years (8.2, 3.4‐13.0 was similar to adults (8.5 (5.4‐11.4). Among all epilepsy cases, 65.1% had active epilepsy. Their (active epilepsy) prevalence was 5.8 (3.5‐8.1). Of them, 63.4% were not receiving treatment. Moreover, those who received allopathy treatment, 72.5% had low adherence leading to a high treatment gap. Significance: Our findings out of this first‐ever national survey were similar to other Asian countries. However, the prevalence of active epilepsy and treatment gap were considerably higher. This study serves useful evidence for tailoring interventions aimed to reduce the burden of epilepsy—primarily through targeted community awareness program—and access to antiepileptic treatment in health facilities in Bangladesh.